2019
DOI: 10.1097/sla.0000000000003002
|View full text |Cite
|
Sign up to set email alerts
|

Disease-free Survival and Local Recurrence for Laparoscopic Resection Compared With Open Resection of Stage II to III Rectal Cancer

Abstract: Laparoscopic assisted resection of rectal cancer was not found to be significantly different to OPEN resection of rectal cancer based on the outcomes of DFS and recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
195
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(231 citation statements)
references
References 12 publications
19
195
2
3
Order By: Relevance
“…They found that LapTME did not meet the criteria for noninferiority in a composite score of complete or near-complete TME, and negative circumferential and distal resection margins (13). It is important to note that Fleshman et al did not nd any difference in survival within two years after surgery (25). Still, the study was not designed as an equivalence trial for survival and recurrence, and the absence of numerical distinctions might not be indicative of any dissimilarity.…”
Section: Discussionmentioning
confidence: 99%
“…They found that LapTME did not meet the criteria for noninferiority in a composite score of complete or near-complete TME, and negative circumferential and distal resection margins (13). It is important to note that Fleshman et al did not nd any difference in survival within two years after surgery (25). Still, the study was not designed as an equivalence trial for survival and recurrence, and the absence of numerical distinctions might not be indicative of any dissimilarity.…”
Section: Discussionmentioning
confidence: 99%
“…As long as TME is performed, low local recurrence rates can be achieved in both open and minimally invasive approaches [16][17][18][19][20]. Oncologic long-term analysis found no statistically significant differences between laparotomy and laparoscopy [21,22]. Application of robotics-assisted low anterior rectal resection with TME results in oncologic outcomes comparable to those of other approaches [23].…”
Section: Radical Surgical Approachmentioning
confidence: 99%
“…In diesem Zusammenhang soll nicht unerwähnt bleiben, dass zwei kürzlich publizierte, randomisierte Studien aus Australien bzw. den USA (ALaCaRT, ACOSOG Z6051) [19,20,21] die Nichtunterlegenheit der laparoskopischen Resektion gegenüber der konventionellen Resektion in Bezug auf pathologische Parameter nicht nachweisen konnten.…”
Section: Epidemiologieunclassified